Performance aspects and physiological responses in male amateur boxing competitions: A brief review - Slimani, M.; Chaabene, H.; Davis, P.; Franchini, E.; Cheour, F.; Chamari, K. (The Journal of Strength and Conditioning Research, 2017)
Boxing is one of the most popular striking combat sports in the world. The aim of this review was to present data concerning performance analysis (time-motion and technical-tactical analysis) and physiological responses (i.e., blood lactate concentration [BLC], heart rate, and oxygen consumption) during novice and elite male simulated and official amateur boxing competitions in any age category. The present review shows that boxing competition is a high-intensity intermittent striking combat sport. Typically, the activity-to-rest ratio was higher in elite (18:1) than in novice (9:1) boxers and significant differences were observed between rounds (first round = 16:1, second round = 8:1, and third round = 6:1) in novice boxers. Thus, total stop-time and total stop-frequency increased over subsequent rounds in novice boxers. The technical-tactical aspects in elite and novice boxing bouts were different between rounds and dependent on the match outcome (i.e., winners vs. losers). Particularly, the current review highlights that triple-punch combinations, total combinations, block- and counter-punch combinations, total punches to the head, technical performance effectiveness, and defensive- and offensive-skills effectiveness may have contributed to win in novice and elite boxing competitions. Higher frequencies of technical movements were also observed in elite compared with novice boxers. From a physiological point of view, BLC increased significantly from postround 1 compared with postround 3 in novice boxing match. BLC was also higher in official than in simulated elite boxing matches in senior compared with junior boxers and in medium heavy-weight category compared with light- and medium-weight categories in junior boxing competition. A higher percentage of maximal heart rate (%HRmax) and maximal oxygen uptake (VO2max) were reported in round 3 compared with rounds 2 and 1 in elite boxing competition. In conclusion, these data are useful for both technical-tactical and physical conditioning sessions. Coaches and fitness trainers are encouraged to adjust their training according to these particular characteristics, specifically in terms of age, participants' level, weight categories, and combat contest type.